Game-assisted learning in physical education for fundamental movement skill development in school-age children: a systematic literature review - Gita Sundari; Anton Komaini; Damrah Damrah; Nuridin Widya Pratono (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The initial search identified 378 records, which were reduced to 364 after duplicate removal. Following title-and-abstract screening, 118 full-text articles were assessed for eligibility, of which 50 met the inclusion criteria for full synthesis. Inclusion criteria comprised English-language original articles published in peer-reviewed journals between 2020 and 2026, addressing motor or psychomotor outcomes operationalized as performance on a validated locomotor, manipulative, or psychomotor assessment instrument within physical activity, physical education, or rehabilitation contexts involving game-based or technology-assisted interventions; exclusion criteria removed conference papers, editorials, and studies lacking such measurable motor outcomes. Title-abstract and full-text screening were conducted independently by two reviewers, with inter-rater agreement quantified using Cohen’s kappa (k = 0.81 and k = 0.86, respectively), and methodological quality of included studies was appraised using the Mixed Methods Appraisal Tool (MMAT). Thematic synthesis revealed four major findings: exergaming and active video games produce consistent short-term gains in gross motor proficiency and muscular fitness; immersive VR and robotic-assisted training enhance task-specific motor control but show limited evidence of transfer to real-world performance; gamified pedagogy increases situational interest, enjoyment, and executive function alongside motor outcomes; and effects are moderated by population characteristics, dosage, and implementation fidelity. These findings carry theoretical implications for motor learning and self-determination frameworks, and practical implications for PJOK curriculum design, teacher training, and inclusive adaptation for learners with special educational needs. Future research should prioritize longer follow-up periods, standardized FMS assessment batteries, and rigorously controlled trials in authentic school settings.